A hysteretic model for the rotational response of embedded column base connections. Issue 115 (December 2018) - Torres-Rodas, Pablo; Zareian, Farzin; Kanvinde, Amit
Abstract: Embedded Column Base (ECB) connections are commonly used in mid- and high-rise steel moment frames, to connect the steel column to the concrete footing. Although recent research has shown these connections to be highly ductile, they are typically designed to be stronger than the adjoining column, resulting in significant cost. To enable assessment of strong-column-weak-base systems that leverage the inherent ductility of these connections, an approach is presented to simulate their hysteretic and dissipative response. The proposed approach simulates ECB connections as an arrangement of two springs in parallel, to reflect moment contributions due to horizontal and vertical bearing stresses. This is informed by recent work that provides physical insight into the internal force transfer within these connections. The springs' response is defined by the pinched Ibarra-Medina Krawinkler (IMK) hysteretic model, which is able to capture both in-cycle and cyclic degradation in strength and stiffness. The model is shown to reproduce the response of ECB connections with reasonable accuracy. Guidelines to calibrate model parameters are presented; these include physics-based estimation of selected parameters such as strength and stiffness, accompanied by empirical calibration of ancillary parameters associated with cyclic deterioration. Limitations are discussed. Highlights: New modeling approach for rotational response of embedded base connections. Considers various forms of deterioration and hysteretic response. Generalizable to various connection configurations. Validated against test data. Balances accuracy with efficiency.